A Study of ‘Akṣara-puruṣottama’ Philosophy in ‘Swāminārāyaṇa-Siddhanta-Sudhā’ - Rao, C. Upender (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The theory of Akṣara-puruṣottama darṣana has been logically established in Swāminārāyaṇa-siddhānta-sudhā, authored by pūjya Sādhu Bhadreśadāsa, the Sanskrit scholar and one of the prominent Mahrāj of the Smāminārāyaṇa tradition in the world. Akṣara-puruṣottama-theory was taught by Parabrahma Sahajānanda which is evolved from Vedic traditions and based on the Sanātana Dharma. This theory was described as a Parāvidyā, Ādhyātma-vidyā, Brahma-jñāna and Brahma-vidyā. Akṣara-Brahma is distinct from the Para-Brahma-Puruṣottama (Nārāyaṇa) who is the source of even Brahma and the cause for its origin. Ātman with the association of Akṣara-Brahman, has to serve the Para-brahma like a servant. This relation between Brahma and Para-Brahman is called ‘Swāmi-sevaka-bhāva’. Akṣara puruṣottama school of philosophy states that akṣara Brahman is distinct from parabrahman unlike the Advaita school of Vedānta. This school is closer to the philosophy of Dvaita vedānta, propounded by the great Pūrṇa Prajña where two distinct entities have been accepted by him.